FAKTOR-FAKTOR YANG MENJADI PERTIMBANGAN HAKIM DALAM MENDAPATKAN HAK ASUH ANAK DAN AKIBAT HUKUM - Sayid Aulia Rahman P. Al-Habsyi (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT       The reasons that led to discord between husband and wife regarding the authority of parenting when child custody has been set by the judge can occur for several reasons, namely: Tension and feel hostility that appear in trial of cases of divorce often leads spouses each hold themselves more deserving custody; Problem child closeness or emotional relationship with one of the parties (mother or father); Problems in the financial matter for child care. Factors - factors underlying the judgment the judge in determining custody of children of divorce are divided into 2 factors, factors Parents: Factors parents in the form of an agreement between the two sides I (husband and wife), a state of mental / moral parents as well as the economic situation of parents; Factors Children: Child factors such as age and the proximity of one of the children with both parents. Constraints faced the judges in determining custody of children of divorce are divided into two factors, namely: factors relating to the proceedings in the trial: factors relating to the proceedings in the court among others, the plaintiff did not submit a request for custody of the child in the lawsuit divorce and one of the parties is not present on the day of the trial has been set. Factors related to the litigants: factors relating to the litigants in the form of one of the parties not known to exist and the child from the marriage between the plaintiff and the defendant who is not in the care of the plaintiff or the defendant.